High-Frequency Repetitive Magnetic Stimulation Enhances the Expression of Brain-Derived Neurotrophic Factor Through Activation of Ca2+–Calmodulin-Dependent Protein Kinase II–cAMP-Response Element-Binding Protein Pathway - Baek, Ahreum; Park, Eun Jee; Kim, Soo Yeon; Nam, Bae-Geun; Kim, Ji Hyun; Jun, Sang Woo; Kim, Sung Hoon; Cho, Sung-Rae (Frontiers in Neurology, 2018)
Repetitive transcranial magnetic stimulation (rTMS) can be used in various neurological disorders. However, neurobiological mechanism of rTMS is not well known. Therefore, in this study, we examined the global gene expression patterns depending on different frequencies of repetitive magnetic stimulation (rMS) in both undifferentiated and differentiated Neuro-2a cells to generate a comprehensive view of the biological mechanisms. The Neuro-2a cells were randomly divided into three groups—the sham (no active stimulation) group, the low-frequency (0.5 Hz stimulation) group, and high-frequency (10 Hz stimulation) group—and were stimulated 10 min for 3 days. The low- and high-frequency groups of rMS on Neuro-2a cells were characterized by transcriptome array. Differentially expressed genes were analyzed using the Database of Annotation Visualization and Integrated Discovery program, which yielded a Kyoto Encyclopedia of Genes and Genomes pathway. Amphetamine addiction pathway, circadian entrainment pathway, long-term potentiation (LTP) pathway, neurotrophin signaling pathway, prolactin signaling pathway, and cholinergic synapse pathway were significantly enriched in high-frequency group compared with low-frequency group. Among these pathways, LTP pathway is relevant to rMS, thus the genes that were involved in LTP pathway were validated by quantitative real-time polymerase chain reaction and western blotting. The expression of glutamate ionotropic receptor N-methyl d-aspartate 1, calmodulin-dependent protein kinase II (CaMKII) δ, and CaMKIIα was increased, and the expression of CaMKIIγ was decreased in high-frequency group. These genes can activate the calcium (Ca2+)–CaMKII–cAMP-response element-binding protein (CREB) pathway. Furthermore, high-frequency rMS induced phosphorylation of CREB, brain-derived neurotrophic factor (BDNF) transcription via activation of Ca2+–CaMKII–CREB pathway. In conclusion, high-frequency rMS enhances the expression of BDNF by activating Ca2+–CaMKII–CREB pathway in the Neuro-2a cells. These findings may help clarify further therapeutic mechanisms of rTMS.